2016
DOI: 10.1128/jb.00023-16
|View full text |Cite
|
Sign up to set email alerts
|

CotG-Like Modular Proteins Are Common among Spore-Forming Bacilli

Abstract: CotG is an abundant protein initially identified as an outer component of the Bacillus subtilis spore coat. It has an unusual structure characterized by several repeats of positively charged amino acids that are probably the outcome of multiple rounds of gene elongation events in an ancestral minigene. CotG is not highly conserved, and its orthologues are present in only two Bacillus and two Geobacillus species. In B. subtilis, CotG is the target of extensive phosphorylation by a still unidentified enzyme and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Our results show that in genomes where CotH is absent, its substrates, CotG and CotB, are also absent [91]. Nevertheless, the role of CotG may be carried out by a non-homologous CotG-like protein with similar structural regions, as previously reported [61]. Other CotH-dependent coat proteins, such as CotC and CotU are conserved in few genomes of the Subtilis group, and they are present when CotH and CotG are present.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results show that in genomes where CotH is absent, its substrates, CotG and CotB, are also absent [91]. Nevertheless, the role of CotG may be carried out by a non-homologous CotG-like protein with similar structural regions, as previously reported [61]. Other CotH-dependent coat proteins, such as CotC and CotU are conserved in few genomes of the Subtilis group, and they are present when CotH and CotG are present.…”
Section: Discussionsupporting
confidence: 78%
“…. For instance, it has been previously reported that CotG is not highly conserved across the Bacillus genus, although its role may be carried out by a non-homologous CotG-like protein that has similar structural regions to CotG [61]. Therefore, we do not rule out the possibility that non-homologous coat-like proteins with similar structural and chemical features may perform the role of poorly conserved coat proteins.…”
Section: Spore-coat-protein Diversity Across Bacillalesmentioning
confidence: 90%
“…Previous studies on the structural characterization of the cotB/cotH/cotG cluster in 128 B. subtilis made use of polar insertional mutations, and it is unclear how the absence of 129 (Giglio et al, 2011, Sacco et al, 1995, Saggese et al, 2016 (Fig. 1 and S1).…”
Section: Spores 127mentioning
confidence: 99%
“…The SKR G region is also predicted to be disordered and may be susceptible to 530 proteolysis (Giglio et al, 2011, Saggese et al, 2016. The repeat region of B. anthracis 531 ExsB, a CotG homologue, was also found to be extremely sensitive to proteolysis 532 of coat proteins following their synthesis in the mother cell, and in promoting the formation 539 of protein complexes competent for assembly (Isticato et al, 2013, Isticato et al, 2015.…”
Section: And Because the Interaction Between Cotg And 523mentioning
confidence: 99%
See 1 more Smart Citation